Deep Fear : The Digital Art Making Based On The Psychological Reaction of Pandemic Phenomenon - Rendy Pandita Bastari; Iqbal Prabawa Wiguna (JURNAL RUPA, 2022)
The Covid 19 pandemic is causing global fall down in almost every aspect, from health, economic, culture, and without exception, psychology, more specifically, on fear. Recent study on psychological impact concluded that specific groups from specific socio-demographic variables would act differently based on their fear of the disease. Every specific group have it’s priorities to survive the pandemic. The mass media also plays a role in driving the fear of people, reported and exaggerating information on the disease. This paper aims to give an artistic approach and respond of the pandemic situation through digital painting and serve as visual artefact of the 2020 pandemic. The method used during the creation process is literature studies on several case studies and relevant theories. The creation begins with phenomenon observation, theoretical approach, conceptualization, and finalizing. The result of the artwork conceptually is that essentially that people fear the most is death which is what being represented through the artwork.